Effectiveness of fluid-viscous dampers for improved seismic performance of inter-storey isolated buildings. (15th August 2018) - Liu, Yanhui; Wu, Jinbiao; Donà, Marco
Highlights: Optimal dampers (FVDs) improve seismic performance of inter-storey isolated buildings. Optimal FVDs effectively reduce isolators/superstructure drift and base shear force. Damper effectiveness strongly depends on the structural non-linear seismic response. A multi-objective optimization algorithm is needed to find optimal parameters of FVDs. Optimizing linear FVDs (simpler) can still lead to reasonable design solutions. Abstract: The use of fluid viscous dampers (FVDs) together with isolators, frequent in near-fault buildings, is effective in reducing displacements of the isolation layer. Such a hybrid system is also beneficial in the case of inter-storey isolation with the aim of limiting P-Δ effects. However, previous research on base isolation shows that this additional damping may also be detrimental, as inter-storey drifts and floor accelerations may increase. This paper analyses the effectiveness of FVDs for enhanced seismic performance of systems with inter-storey isolation. A seven-floor building, with natural and lead rubber bearings between the second and third levels, was used as a case study, and a multi-objective optimal design was performed to identify the best damper parameters. In particular, time-history analyses with various natural records were carried out and two competing objectives were examined: minimisation of the deflection of the isolation layer and minimisation of the total drift of the superstructure. The results show not only the effectiveness of optimal FVDs but also the fact that their optimal linearity degree depends to a great extent on the non-linear seismic response of the structure, i.e., on the type of earthquake. The simplest design approach, consisting of applying an optimization algorithm for each design accelerogram, did not seem, in this case, to be sufficient to identify the best overall design solution. The design consequences of these findings are discussed.